A Study on the Clinical Presentation of Patients with Hypothyroidism - Mahmood, I; Hasan, AMS; Rahman, MK; Khan, MMR; Haque, M Azizul; Chowdhury, MMH; Iqbal, A; Tushar, AZ; Ali, SM (TAJ: Journal of Teachers Association, 2019)
This study has the intention to look for the common signs and symptoms of hypothyroidism in persons with clinical diagnosis of hypothyroidism that was confirmed by laboratory tests. This retrospective study was undertaken at Pabna, Bangladesh, from July 2009 to November 2010 among 54 patients with hypothyroidism visiting Medicine Department of 250 bedded Pabna General Hospital and private chamber of the author. Patients belonged to some parts of Pabna, Natore, Serajganj and Kushtia Districts. All cases with probable diagnosis of hypothyroidism based on the signs and symptoms were included in the study. Patients who completed questionnaires (n=54) were interviewed three times during this period. Female/male ratio was 9.3/1. The most common symptoms were lethargy, weight gain, cold intolerance and menorrhagia. The most common signs were puffy face and pallor. Severe disease was noticed in 3.7%. Mild type was the most common presentation of hypothyroidism (66.67%). The most common signs and symptoms of hypothyroidism at Pabna and surrounding districts were different from other studies. Socio-demographic and nutritional status, illiteracy level and personal care are among the probable causes. Unfortunately, concomitance of some of the signs and symptoms are not diagnostic for hypothyroidism. It seems that strong clinical suspicion and laboratory confirmation are the only reliable methods for hypothyroidism diagnosis. TAJ 2010; 23(1): 51-54